Thermal transient behavior of an ANG storage during dynamic discharge phase at room temperature - Ridha, Firas Noori; M. Yunus, Rosli; Rashid, Mohd.; Ismail, Ahmad Fauzi (Elsevier Ltd, 2007)
Throughout this work the thermal behavior of an adsorptive natural gas (ANG) storage under dynamic discharge conditions at room temperature of 27 C was studied. The work was conducted in a gravimetrically built experimental unit where the storage chamber was equipped with axial and radial distributed thermocouples and the storage was discharged at different discharge rates. The results demonstrated that maximum methane discharge rate of 5 L min1 in activated carbon/methane system resulted in the severest temperature drop corresponding to further drop of about 40% compared to that at 1 L min-1. This extreme thermal condition claimed a reduction of 15.2% in methane dynamic delivery capacity with respect to the isothermal delivery capacity. Ethane and propane have high enthalpies of desorption, and hence high portions of these gases may influence the performance of ANG storages through their thermal impact. A gas mixture with 14.98% and 14.54% volumes of ethane and propane resulted in higher temperature drop than methane claiming a reduction of 19.4% in the dynamic delivery capacity comparing with methane delivery capacity